Scaling up Vulture Safe Zone to conserve a greater number of Endangered raptor species: A case for creating a Raptor Safe Zone in Nepal - Chaudhary, Anand (Nepalese Journal of Zoology, 2023)
Nepal has successfully piloted the Vulture Safe Zone, a broad-scale conservation strategy for Endangered vulture species. An obvious question is: what more can we do to build on this accomplishment? Through this paper, I advocate for expanding the Vulture Safe Zones to include other threatened raptors to create Raptor Safe Zones (RSZs). RSZs are a logical next step for Nepal because this country is a global hotspot for raptors and because the RSZ will help conserve 23 threatened raptor species, both within and beyond existing protected areas. I discuss opportunities, challenges, and the way forward for creating RSZ.